Social anxiety disorders in clinical practice: differentiating social phobia from avoidant personality disorder. (August 2015) - Lampe, Lisa
Objective: To outline the problems around overlap between social phobia (SAD) and avoidant personality disorder (AVPD) and provide guidelines that may assist clinicians to differentiate these conditions. Conclusions: A constellation of symptoms can be identified that may distinguish AVPD from SAD, with key features being a strong and pervasively negative self-concept, a view of rejection as equating to a global evaluation of the individual as being of little worth and a sense of not fitting in socially that dates from early childhood. It is important to identify the presence of AVPD in order to anticipate potential problems with engagement and retention in therapy, to target treatment interventions and optimise outcome.